Role of Family Motivation, Workplace Civility and Self-Efficacy in Developing Affective Commmitment and Organizational Citizenship Behavior (2020)
The mechanism connecting the antecedents to positive attitudes like affective commitment (AC) and positive behaviors like organizational citizenship behavior (OCB) is an under-researched area in the field of positive organizational scholarship. Drawing on Social Exchange Theory (SET), this study empirically validates family motivation and civility as antecedents of affective commitment and organizational citizenship behavior through the mediating mechanism of self-efficacy. The process by Hayes (2013) was used to analyze time-lagged and multi-source data collected from 335 employees of educational and telecom sector. Results indicate that the relationship of affective commitment with family motivation and civility is partially mediated whereas the relationship of organizational citizenship behavior with family motivation and civility is fully mediated by self-efficacy. This study adds to the literature of family-work enrichment accounts by validating family motivation as a novel antecedent for positive behavioral outcomes. The implications of the study are discussed.